Need Assessment: A Survey of Principals’, Primary and Intermediate Teachers’ Perception of the Counsellor’s Role in B.C.’s Elementary Schools9 - Allan, John; Doi, K.; Reid, C. (Canadian Journal of Counselling and Psychotherapy, 2012)
In order to assess the need for counsellors in B.C.'s elementary schools, a questionnaire was sent to the principal, a primary and an intermediate teacher in 150 schools randomly distributed throughout the province. The return rate was 83%. The results indicated that most respondents: ( 1 ) wanted the services of a counsellor at least 2-3 days a week, (2) preferred a school-based teacher-counsellor to a counsellor coming into the school, (3) thought counsellors ought to be trained in developmental, preventive and remedial approaches, (4) believed counsellors ought to provide direct services to teachers and students alike and (5) perceived the counsellor's role in regards to parents as that of a consultant. Comparisons are made with other studies and some implications for school counsellors and counsellor educators are raised.